Effective Stance in Conservative Newspaper Opinion Articles on Irregular Immigration and Refugee Humanitarian Crises - Marta Carretero; Elena Domínguez Romero (Revista Alicantina de Estudios Ingleses)
This paper presents a quantitative and contrastive analysis of expressions of effective stance in conservative newspaper opinion articles related to irregular immigration and humanitarian crises involving refugees in both English and Spanish contexts. Drawing upon the seminal works of Langacker (2013) and Marín-Arrese (2021a, 2021b, 2023), the study examines six fundamental categories of effective stance expressions established according to factors such as orientation towards self or others, degree of control about the realisation of the event, and agreement with social norms. The dataset under examination comprises a 120,000-word corpus of opinion articles obtained from two conservative newspapers, The Telegraph from the United Kingdom and El Mundo from Spain. The words are evenly distributed, with each newspaper contributing 30,000 words in articles pertaining to three humanitarian crises involving refugees: Syria (2015), Afghanistan (2021), and Ukraine (2022-2023), and 30,000 words relating to articles on irregular immigration coinciding in time with each of the three refugee crises. The primary objective of the paper is to discern notable differences between the two newspapers and across the different refugee and irregular immigration crises under investigation. The analysis of the results, which uncover a larger number of effective stance expressions in the English subcorpus as well as distributional differences of subcategories across the subcorpora in both languages, provides a valuable understanding of the intricate patterns of usage and distribution of effective stance expressions within the realm of newspaper discourse, thereby enriching our comprehension of journalistic portrayals concerning the complexity of refugee crises and migratory movements.